Styrene-acrylic emulsion and its manufacturing method, negative electrode sheet, secondary battery, and power consumption device
Patent Information
- Application Number
- JP2023559066
- Authority / Receiving Office
- JP · JP
- Patent Type
- Patents
- Current Assignee / Owner
- Filing Date
- 2022-06-16
- Publication Date
- 2025-03-13
- Estimated Expiration
- 2042-06-16
AI Technical Summary
【0020】 従来技術に対して、本願は少なくとも以下の有益な効果を含む。
Smart Images

Figure 0007645033000003 
Figure 0007645033000004 
Figure 0007645033000005
Abstract
Description
[Technical field]
[0001] The present application relates to the technical field of secondary batteries, and more particularly to a styrene-acrylic emulsion and its manufacturing method, a negative electrode sheet, a secondary battery, and a power consuming device. [Background technology]
[0002] 2. Description of the Related Art Secondary batteries have excellent characteristics such as light weight, non-pollution, and no memory effect, and are therefore widely used in various consumer electronic products and electric vehicles.
[0003] At present, hard carbon materials can be used as the negative electrode active material in secondary batteries such as lithium ion batteries and sodium ion batteries. Hard carbon materials have the advantages of low energy storage voltage, high capacity and good cycle stability, as well as abundant sources and simple manufacturing processes, and are currently one of the most applicable negative electrode materials, with large application markets for both lithium ion batteries and sodium ion batteries. Summary of the Invention
[0004] In view of the technical problems existing in the background art, the present application aims to provide a negative electrode sheet containing a hard carbon material that can combine good adhesive strength, cohesive strength, and flexibility, and to provide a secondary battery including the negative electrode sheet with good cycle stability.
[0005] To achieve the above object, a first aspect of the present application provides a styrene-acrylic emulsion, in which the Dv50 particle size of latex particles in the styrene-acrylic emulsion is 350-900 nm, preferably 350-800 nm.
[0006] In any embodiment of the present application, the latex particles are styrene acrylate copolymers, and the glass transition temperature of the styrene acrylate copolymers is 10-70°C, preferably 10-60°C.
[0007] A second aspect of the present application provides a method for producing the styrene acrylic emulsion provided in the first aspect of the present application, the method comprising the steps of: preparing a pre-emulsion by mixing a portion of an emulsifier, a portion of an acrylic ester monomer, and a portion of a styrene monomer with water; mixing another portion of the emulsifier, another portion of the acrylic acid ester monomer, and another portion of the styrene monomer with water, and adding an initiator to start polymerization to prepare a seed emulsion; adding the pre-emulsion to the seed emulsion in a dropwise manner, and adding an initiator to carry out a polymerization reaction to prepare a styrene-acrylic emulsion having a latex particle Dv50 particle size of 350-900 nm; The total mass of the emulsifier is 0.7%-5%, preferably 1%-4.5%, of the total mass of the prepared monomers, and the prepared monomers include acrylate monomers and styrene monomers.
[0008] In any embodiment of the present application, the styrene acrylic emulsion comprises, by weight percentage, 30%-80% styrene-based monomer, 20%-70% acrylate-based monomer, and 0%-10% functional monomer, based on the total weight of the prepared monomers.
[0009] Preferably, the functional monomer is added in the step of preparing the pre-emulsion and / or the seed emulsion.
[0010] Preferably, the functional monomer is at least one of an acrylic monomer, a phosphate monomer, and a fluorine-containing acrylate monomer.
[0011] A third aspect of the present application provides a negative electrode sheet, comprising: a negative electrode current collector; and a negative electrode active material layer located on at least one surface of the negative electrode current collector, wherein components of the negative electrode active material layer include a hard carbon material and an adhesive derived from the styrene-acrylic emulsion according to the first aspect of the present application.
[0012] In any embodiment of the present application, the components of the negative electrode active material layer further include a conductive agent and a dispersant, and in the negative electrode active material layer, the hard carbon material is 85%-97% by mass, the styrene-acrylic acid ester copolymer is 1%-8% by mass, the conductive agent is 0.3%-5% by mass, and the dispersant is 0.5%-4% by mass.
[0013] In any embodiment of the present application, the coating weight of the negative electrode active material layer is 2-13 mg / cm 2 and preferably 5-12 mg / cm 2 It is.
[0014] In any embodiment of the present application, the hard carbon material is at least one of irregularly shaped particles, spherical particles, and approximately spherical particles, and preferably, the hard carbon material is irregularly shaped particles.
[0015] In any embodiment of the present application, the particle size of the hard carbon material, Dv50, is 1-10 μm, preferably 4-9 μm.
[0016] In any embodiment of the present application, the hard carbon material is irregularly shaped particles, the adhesive strength between the negative electrode active material layer and the negative electrode current collector is 10-40 N / m, and the cohesive strength of the negative electrode active material layer is 150-800 N / m.
[0017] In any embodiment of the present application, the hard carbon material is at least one of spherical particles and nearly spherical particles, the adhesive strength between the negative electrode active material layer and the negative electrode current collector is 10-30 N / m, and the cohesive strength of the negative electrode active material layer is 150-600 N / m.
[0018] A fourth aspect of the present application provides a secondary battery including the negative electrode sheet provided in the third aspect of the present application.
[0019] A fifth aspect of the present application provides a power consuming device including the secondary battery provided in the fourth aspect of the present application.
[0020] Compared with the prior art, the present application includes at least the following beneficial effects:
[0021] The present application provides a styrene-acrylic emulsion with a particle size of Dv50 of 350-900nm, and creatively uses it as an adhesive to improve the problems of adhesion, cohesion and flexibility of a negative electrode sheet manufactured using a hard carbon material as a negative electrode active material. The negative electrode active material layer of the above negative electrode sheet of the present application employs a hard carbon material as a negative electrode active material, and employs a styrene-acrylic acid ester copolymer with a particle size Dv50 of latex particles in a specific range as an adhesive for the negative electrode active material layer, and the latex particles in the styrene-acrylic emulsion as an adhesive have a large particle size and are dispersed and not aggregated, so that the effective adhesion between the hard carbon material and the negative electrode current collector and the inside of the hard carbon material can be effectively improved, and the adhesion between the hard carbon material and the negative electrode current collector and the cohesion between the hard carbon material and the hard carbon material can be improved. In this way, the negative electrode sheet not only improves the adhesive strength between the negative electrode active material layer and the negative electrode current collector and the cohesive strength of the negative electrode active material layer, but also has excellent flexibility, and even when the coating weight of the negative electrode active material layer is high, the negative electrode sheet can still maintain high adhesive strength and flexibility. The negative electrode sheet of the present application is applied to a secondary battery, does not affect the energy performance of the battery, ensures the stability of the performance of the negative electrode sheet, and provides the secondary battery with good cycle stability. [Brief description of the drawings]
[0022] In order to more clearly describe the technical solution of the present application, the drawings used in the present application are briefly described below. Obviously, the drawings described below are only some embodiments of the present application, and those skilled in the art can also obtain other drawings based on the drawings without creative efforts. [Figure 1] 1 is a scanning electron microscope photograph of a negative electrode sheet according to an embodiment of the present application. [Diagram 2] 1 is a schematic diagram of an embodiment of a secondary battery. [Diagram 3] FIG. 3 is an exploded view of FIG. [Figure 4] FIG. 2 is a schematic diagram of an embodiment of a battery module. [Diagram 5] 1 is a schematic diagram of an embodiment of a battery pack. [Figure 6] FIG. 6 is an exploded view of FIG. [Figure 7] 1 is a schematic diagram of an embodiment of a power consuming device that uses a secondary battery as a power source.
[0023] Symbols: 1: battery pack, 2: upper housing, 3: lower housing, 4: battery module, 5: secondary battery, 51: case, 52: electrode assembly, 53: cover plate, 6: power consuming device. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS
[0024] The present application will now be further described with reference to specific embodiments, which should be understood to be merely illustrative of the present application and not limiting the scope of the present application.
[0025] For the sake of brevity, this specification specifically discloses only some numerical ranges. However, any lower limit can be combined with any upper limit to form a range not expressly described, and any lower limit can be combined with another lower limit to form a range not expressly described, and similarly any upper limit can be combined with another upper limit to form a range not expressly described. Also, each disclosed point or single numerical value can be combined with any other point or single numerical value as a lower limit or upper limit, or can be combined with another lower limit or upper limit to form a range not expressly described.
[0026] In the description of this specification, unless otherwise specified, the terms "more than or equal to" and "less than or equal to" are inclusive of the number, and "multiple types" in "one type or multiple types" means two or more types.
[0027] In the description of this specification, unless otherwise stated, the term "or" is inclusive. That is, the phrase "A or B" means "A, B, or both A and B". More specifically, A is true (or exists) and B is false (or does not exist), or A is false (or does not exist) and B is true (or exists), or both A and B are true (or exist), all of which satisfy the condition "A or B". Unless otherwise stated, the terms used in this application have the known meanings that are commonly understood by those skilled in the art. Unless otherwise stated, the numerical values of each parameter mentioned in this application can be measured by various measurement methods commonly used in the field (for example, can be measured by the method provided in the examples of this application).
[0028] Hard carbon material is a negative electrode active material of secondary batteries, and is characterized by hard carbon being crystal-dispersed, large lattice spacing, sheet layers being mainly chemically bonded to each other, hard carbon particles being mainly mechanically riveted to each other, and a large specific surface area. However, due to these characteristics of hard carbon particles, the adhesive strength of the hard carbon negative electrode sheet is very low, which is more noticeable when the coating weight of the negative electrode active material layer is large, and this makes the negative electrode sheet prone to decarbonization during the coating process, resulting in the problem of being unable to continue normal production.
[0029] Currently, some techniques are trying to improve the adhesive strength of the negative electrode sheet containing hard carbon material. For example, water-soluble adhesives such as polyacrylamide copolymers with strong adhesive strength are used, but such methods result in high rigidity and brittleness of the negative electrode sheet, which breaks during cold pressing and causes problems of winding cracks, and such methods also have limitations in improving the adhesive strength. In addition, there are techniques to improve the adhesive strength of the negative electrode sheet by significantly increasing the amount of adhesive used, but increasing the amount of adhesive used results in a loss of energy density of the battery. In addition, some conventional adhesives such as styrene butadiene rubber (SBR), water-based acrylic resin, polyvinylidene fluoride (PVDF), polytetrafluoroethylene (PTFE), ethylene-vinyl acetate copolymer (EVA), polyvinyl alcohol (PVA), and polyvinyl butyral (PVB) cannot solve the above problems, so how to achieve good adhesive strength, cohesion, and flexibility in the negative electrode sheet containing hard carbon material is an issue that needs to be solved as soon as possible.
[0030] [Styrene acrylic emulsion] The present application provides a styrene-acrylic emulsion used as an adhesive for a negative electrode active material layer, which can solve the problem of achieving good adhesive strength, cohesive strength, and flexibility in a negative electrode material that uses a hard carbon material as the negative electrode active material.
[0031] The present application provides a styrene-acrylic emulsion, in which the latex particles in the styrene-acrylic emulsion have a Dv50 particle size of 350-900 nm, in which the latex particles are styrene-acrylic acid ester copolymers.
[0032] Generally, in order to ensure high stability and long-term storage of styrene-acrylic emulsions, the Dv50 particle size of the latex particles in most styrene-acrylic emulsions is 300 nm or less at present, and the conventional idea for improving the adhesive strength of negative electrode sheets is to reduce the particle size of the emulsion adhesive as much as possible and increase the specific surface area to improve the adhesive strength of the electrode sheet.
[0033] The styrene acrylic acid ester copolymer in the styrene acrylic emulsion provided by the present application is spherical and has a larger particle size, for example, the particle size of Dv50 of the present application is 350-900 nm, and exists stably. In addition, when latex particles having a particle size in a specific Dv50 range are adopted, the latex particles in the styrene acrylic emulsion as the adhesive for the styrene acrylic acid ester copolymer negative electrode active material layer have a large particle size and are well dispersed and do not aggregate, so that the effective adhesion between the hard carbon material and the negative electrode current collector and the inside of the hard carbon material can be effectively improved, and the adhesive strength between the hard carbon material and the negative electrode current collector and the cohesive strength between the hard carbon material and the hard carbon material can be improved. In this way, the negative electrode sheet not only improves the adhesive strength between the negative electrode active material layer and the negative electrode current collector and the cohesive strength of the negative electrode active material layer, but also has excellent flexibility, and even when the coating weight of the negative electrode active material layer is high, the high adhesive strength and flexibility of the negative electrode sheet can still be maintained. The negative electrode sheet of the present application is applied to a secondary battery, does not affect the energy performance of the battery, ensures the stability of the performance of the negative electrode sheet, and provides the secondary battery with good cycle stability.
[0034] The present application further provides a method for preparing a styrene-acrylic emulsion, comprising the following steps S11-S13:
[0035] Step S11: Pre-emulsification process. Mix some emulsifier, some acrylic ester monomer, and some styrene monomer with water, and add functional monomer as needed to prepare a homogeneous, stable, and non-phase-separated pre-emulsion.
[0036] In some embodiments, the mixing temperature in step S11 is 30° C.-80° C., and the mixing time is 0.5 h-2 h.
[0037] Step S12: Prepare a seed emulsion. Mix another part of an emulsifier, another part of an acrylate monomer, and another part of a styrene monomer with water, add a functional monomer if necessary, and then add a part of an initiator to start polymerization to obtain a seed emulsion.
[0038] In some embodiments, in step S12, the mixing temperature is 50° C.-90° C., the mixing time is 0.1 h-1 h, and 1 / 4 of the initiator is added to start the polymerization to obtain a seed emulsion.
[0039] Step S13: Continuous dropping step. The pre-emulsion prepared in step S11 is added to the seed emulsion prepared in step S12 in a dropping manner, and another part of the initiator is added to carry out a polymerization reaction to prepare a styrene-acrylic emulsion with a Dv50 particle size of 350-900 nm.
[0040] The preparation monomers of the above styrene acrylic emulsion include acrylate monomers and styrene monomers, and may also include functional monomers as necessary. As mentioned above, the functional monomers are added in the steps of preparing the pre-emulsion and / or the seed emulsion. In other words, the functional monomers may be added in the steps of preparing the pre-emulsion or the seed emulsion, or may be added in both steps, respectively.
[0041] Here, the total mass of the emulsifier is 0.7%-5% of the total mass of the prepared monomer. The amount of the emulsifier used can be mainly adjusted to adjust the Dv50 particle size of the latex particles in the styrene-acrylic emulsion. Furthermore, the mass of the emulsifier is 1%-4.5% of the total mass of the prepared monomer.
[0042] In some embodiments, the pre-emulsion is controlled to drip within 1-5 hours.
[0043] In some embodiments, after adding the initiator in step S13, the temperature of the reaction system is controlled at 50° C.-90° C., and the incubation time is controlled at 1-4 h to further polymerize the unreacted free monomers.
[0044] Furthermore, the amount of each raw material used other than the initiator in step S11 is 3 / 4-2 / 3 of the total mass of the corresponding raw material. Correspondingly, the amount of each raw material used other than the initiator in step S12 is 1 / 4-1 / 3 of the total mass of the corresponding raw material.
[0045] In step S12, the amount of the initiator used is 1 / 4-1 / 3 of the total mass of the initiator. In step S13, the amount of the initiator used is 3 / 4-2 / 3 of the total mass of the initiator.
[0046] In addition, in step S13, another part of the initiator is added to carry out a polymerization reaction, followed by cooling, adjusting the pH value of the system to 6-9 using a pH adjuster, and filtering to obtain a styrene-acrylic emulsion.
[0047] In some embodiments, the preparation monomers of the styrene-acrylic emulsion include, by mass percentage, 30%-80% styrene-based monomer, 20%-70% acrylate-based monomer, and 0%-10% functional monomer. The functional monomer is at least one of an acrylic monomer, a phosphoric acid ester-based monomer, and a fluorine-containing acrylate-based monomer. The functional monomer plays a role in improving the stability of the styrene-acrylic emulsion and improving the mechanical performance of the adhesive film formed by using the styrene-acrylic emulsion as an adhesive.
[0048] In addition, the preparation monomers of the styrene-acrylic emulsion include, by mass percentage, 30%-80% styrene-based monomer, 19%-70% acrylate-based monomer and 1%-10% functional monomer.
[0049] Styrenic monomers include styrene and its derivatives. Further, derivatives of styrene include alkyl-substituted styrenes. In some embodiments, the styrenic monomer may be selected from styrene and methylstyrene, and styrene may be selected.
[0050] The acrylic acid ester monomer is a general term for esters of acrylic acid and esters of the same kind of acrylic acid. In some embodiments, the acrylic acid ester monomer may be at least one selected from acrylic acid C1-C16 alkyl ester and methacrylic acid C1-C16 alkyl ester. The acrylic acid ester monomer includes, but is not limited to, at least one of methyl acrylate, methyl methacrylate, ethyl acrylate, ethyl methacrylate, butyl acrylate, butyl methacrylate, hexyl acrylate, hexyl methacrylate, isooctyl acrylate, isooctyl methacrylate, n-butyl acrylate, isobutyl acrylate, 2-ethylhexyl acrylate, 2-ethylhexyl methacrylate, hydroxypropyl acrylate, hydroxyethyl acrylate, N,N-dimethylaminoethyl acrylate, N,N-dimethylaminopropyl methacrylate, N,N-dimethylaminopropyl acrylate, N,N-dimethylaminoethyl acrylamide, N,N-dimethylaminopropyl acrylamide, and acrylonitrile.
[0051] Additionally, the acrylate monomer may be at least one of methyl acrylate, methyl methacrylate, and n-butyl acrylate.
[0052] In some embodiments, the functional monomer comprises at least one of an acrylic monomer, a phosphate ester monomer, and a fluorine-containing acrylate monomer.
[0053] Acrylic monomers include at least one of acrylic acid and its homologs, including, but not limited to, at least one of methacrylic acid and acrylic acid.
[0054] The phosphate ester monomer is an ester derivative of phosphoric acid. The phosphate ester monomer includes, but is not limited to, at least one of polyfunctional acid acrylic acid ester phosphate, alkyl acrylic acid ester phosphate, ethylene glycol methacrylate phosphate, 2-hydroxyethyl methacrylate phosphate, siloxane phosphate, 2-hydroxyethyl methacrylate phosphate, vinyl alkoxy phosphate (PAM100), methacrylate alkoxy phosphate (PAM200), monofunctional acrylic acid phosphate (PAM300), hydroxyethyl methacrylate phosphate (PAM4000), alkyl phosphate ester special monomer (PAM5000), COPS-3, alkyl (aryl) phosphate, aliphatic alcohol (alkylphenol) polyoxyethylene ether phosphate, alkyl alcohol amide phosphate, imidazoline phosphate, hydroxyethyl phosphate, polymeric polyphosphate, and siloxane phosphate.
[0055] The fluorine-containing acrylate monomer is an acrylate monomer that contains fluorine. The fluorine-containing acrylates include, but are not limited to, perfluoroalkyl (meth)acrylates. The perfluoroalkyl (meth)acrylates include, but are not limited to, at least one of perfluorooctylethyl acrylate, perfluorohexylethyl acrylate, and perfluoropolyether methacrylate.
[0056] In some embodiments, the functional monomer is a phosphate ester such as methacrylic acid, acrylic acid, perfluorooctylethyl acrylate, perfluorohexylethyl acrylate, perfluoropolyether methacrylate, polyfunctional acid acrylate phosphate, alkyl acrylate phosphate, ethylene glycol methacrylate phosphate, 2-hydroxyethyl methacrylate phosphate, alkyl phosphate-based specialty monomers, siloxane phosphate, phosphate ester, 2-hydroxyethyl methacrylate phosphate, vinyl alkoxy phosphate (PA M100), methacrylate alkoxy phosphate (PAM200), monofunctional acrylic phosphate (PAM300), hydroxyethyl methacrylate phosphate (PAM4000), alkyl phosphate special monomer (PAM5000), COPS-3, alkyl (aryl) phosphate, aliphatic alcohol (alkylphenol) polyoxyethylene ether phosphate, alkyl alcohol amide phosphate, imidazoline phosphate, hydroxyethyl phosphate, polymeric polyphosphate, and siloxane phosphate.
[0057] Furthermore, the functional monomer may be at least one selected from acrylic acid, acrylate phosphate, and perfluorooctylethyl acrylate.
[0058] In some embodiments, the emulsifier is a member selected from a reactive emulsifier, an anionic emulsifier, and a nonionic emulsifier.
[0059] Further reactive emulsifiers include, but are not limited to, one or more mixtures of allyloxynonylphenol polyoxyethylene ether ammonium sulfate (KL-100), allyloxyhydroxypropyl sulfonate sodium (COPS-1), 2-propenylphthalamido-2-methylpropane sulfonic acid (AMPS), SR-10, 3-allyloxy-1-hydroxy-propane sulfonate, 2-acrylamido-2-methylpropane sulfonate sodium, 3-allyloxy-1-hydroxy-propane phosphate, sodium vinyl sulfonate, fatty alcohol ether vinyl sulfonate sodium salt, decaperfluorononanoic acid amine, sodium dodecyl diphenyl ether disulfonate (2A1), SR-10, 1-allyloxy-3-(4-nonylphenol)-2-propanol polyoxyethylene (10) ether ammonium sulfate, ER-10, and sodium vinyl sulfonate. Furthermore, the reactive emulsifier may be at least one selected from allyloxynonylphenol polyoxyethylene ether ammonium sulfate (KL-100) and sodium allyloxyhydroxypropyl sulfonate (COPS-1).
[0060] In addition, the anionic emulsifier includes, but is not limited to, one or more mixtures of nonylphenol polyether sulfosuccinic acid monoester sodium salt (A-103), nonylphenol polyoxyethylene ether sulfate ammonium salt (CO-436), dialkyl sodium sulfate (SLS), sodium dodecyl sulfonate (SDS), sodium dodecyl benzene sulfonate (SDBS), allyl polyoxyethylene ether ammonium sulfate, and sodium stearate. In addition, the anionic emulsifier can be selected from nonylphenol polyether sulfosuccinic acid monoester sodium salt (A-103).
[0061] Further, the nonionic emulsifier includes, but is not limited to, one or more mixtures of polyoxyethylene sorbitan monolaurate (TW-20), polyoxyethylene sorbitan monooleate (TW-80), polyoxyethylene ether, Span, Tween, allyl polyoxyethylene ether, vinyl polyoxyethylene ether. Preferably, the nonionic emulsifier is at least one selected from polyoxyethylene sorbitan monolaurate (TW-20) and polyoxyethylene sorbitan monooleate (TW-80).
[0062] In some embodiments, the initiator is at least one selected from potassium persulfate, sodium persulfate, and ammonium persulfate.
[0063] In some embodiments, the pH adjuster is at least one selected from sodium hydroxide, potassium hydroxide, ammonium hydroxide, N,N-dimethylethanolamine, sodium bicarbonate, and sodium carbonate, and sodium hydroxide can be selected.
[0064] In some embodiments, the styrene acrylic emulsion prepared has a solids content of 35%-50%, a viscosity at 25° C. of 10-60 mPa·s, and a pH of 6-9.
[0065] [Secondary battery] A secondary battery is a battery that can be used continuously by activating the active material through charging after discharging.
[0066] Generally, a secondary battery includes a positive electrode sheet, a negative electrode sheet, a separator, and an electrolyte. During the charge and discharge process of the battery, active ions shuttle between the positive electrode sheet and the negative electrode sheet to be inserted and removed. The separator is provided between the positive electrode sheet and the negative electrode sheet to serve as an insulator. The electrolyte serves to conduct ions between the positive electrode sheet and the negative electrode sheet.
[0067] [Negative electrode sheet] In the secondary battery, the negative electrode sheet usually includes a negative electrode current collector and a negative electrode active material layer provided on at least one surface of the negative electrode current collector, and the negative electrode active material layer includes a hard carbon material and an adhesive derived from the above-mentioned styrene-acrylic emulsion of the present application. That is, the latex particles (styrene-acrylic acid ester copolymer) in the above-mentioned styrene-acrylic emulsion are used as an adhesive, and the Dv50 particle size of the latex particles is 350-900 nm.
[0068] Without being limited to any theory, the negative electrode active material layer of the negative electrode sheet of the present application adopts a hard carbon material as the negative electrode active material, and adopts a styrene acrylic acid ester copolymer with a particle size of latex particles in a specific Dv50 range as an adhesive for the negative electrode active material layer. The styrene acrylic acid ester copolymer as an adhesive has a large particle size, good dispersion, and does not aggregate, so that it can effectively improve the effective adhesion between the hard carbon material and the negative electrode current collector, and the inside of the hard carbon material, and can improve the adhesive force between the hard carbon material and the negative electrode current collector, and the cohesive force between the hard carbon material and the hard carbon material. In this way, the negative electrode sheet not only improves the adhesive force between the negative electrode active material layer and the negative electrode current collector, and the cohesive force of the negative electrode active material layer, but also has excellent flexibility, and even when the coating weight of the negative electrode active material layer is high, the high adhesive force and flexibility of the negative electrode sheet can still be maintained. The negative electrode sheet of the present application is applied to a secondary battery, does not affect the energy performance of the battery, ensures the stability of the performance of the negative electrode sheet, and provides the secondary battery with good cycle stability.
[0069] The negative electrode current collector can be a conventional metal foil or a composite current collector (e.g., a metal material can be applied to a polymer substrate to form a composite current collector). As an example, the negative electrode current collector can be a copper foil.
[0070] The negative electrode active material layer is obtained by applying a negative electrode slurry containing a hard carbon material and the styrene-acrylic emulsion of the present application to a negative electrode current collector, and then going through processes such as drying, cold pressing, cutting, etc. In this process, the hard carbon material is used as the negative electrode active material, and the styrene-acrylic emulsion is used as an adhesive.
[0071] The negative electrode slurry may contain a conductive agent and other optional auxiliary agents as necessary. The negative electrode slurry is used to form a negative electrode active material layer on a negative electrode current collector. It is understood that the negative electrode slurry further contains a solvent.
[0072] In addition, the manufacturing process of the negative electrode sheet is simple and the cost is low.
[0073] Preferably, the Dv50 particle size of the styrene acrylic acid ester copolymer in the negative electrode sheet may be 350 nm, 400 nm, 450 nm, 500 nm, 600 nm, 700 nm, 800 nm, or 900 nm. Furthermore, the Dv50 particle size of the styrene acrylic acid ester copolymer in the negative electrode sheet is 350-800 nm. Within this further selected range, the negative electrode sheet produced has better flexibility, adhesion, and cohesion, and the secondary battery produced has a smaller DCR and better cycle performance, and a smaller DCR indicates a better large current discharge capacity, so that the secondary battery can have both good cycle stability and large current discharge capacity.
[0074] In some embodiments, the components of the negative electrode active material layer further include a conductive agent and a dispersant.
[0075] Furthermore, in the negative electrode active material layer, the hard carbon material is 85%-97%, the styrene acrylic acid ester copolymer is 1%-8%, the conductive agent is 0.3%-5%, and the dispersant is 0.5%-4%, by mass percentage. By adopting such a combination of the hard carbon material and the styrene acrylic acid ester copolymer, it is possible to improve the adhesive strength between the negative electrode active material layer and the negative electrode current collector and the cohesive strength of the negative electrode active material layer without increasing the amount of the styrene acrylic acid ester copolymer used as the adhesive.
[0076] Furthermore, in the negative electrode active material layer, the styrene-acrylic acid ester copolymer is contained in a content of 2% to 5% by mass.
[0077] In some embodiments, the coating weight of the negative electrode active material layer is 2-13 mg / cm 2 For example, 2 mg / cm 2 , 5 mg / cm 2 , 7 mg / cm 2 , 8 mg / cm 2 , 10mg / cm 2 , 11 mg / cm 2 , 12 mg / cm 2 , 13 mg / cm 2 The use of a combination of a hard carbon material and a styrene acrylic acid ester copolymer in this way can be applied even when the coating weight of the negative electrode active material layer is large, and satisfies the requirements for adhesive strength and cohesive strength. Preferably, the coating weight of the negative electrode active material layer is 5-12 mg / cm 2 It is.
[0078] By way of example, the conductive agent may be one or more of superconducting carbon, acetylene black, carbon black, ketjen black, carbon dots, carbon nanotubes, graphene, and carbon nanofibers.
[0079] As an example, the dispersant may be sodium carboxymethylcellulose CMC-Na. Furthermore, the negative electrode active material layer may contain other optional auxiliary agents, such as a PTC thermistor material.
[0080] In some embodiments, the glass transition temperature Tg of the latex particles (styrene acrylic acid ester copolymer) in the styrene acrylic emulsion used is 10-70°C. The glass transition temperature of the styrene acrylic acid ester copolymer is related to the monomer ratio of the styrene acrylic acid ester. Therefore, the glass transition temperature of the styrene acrylic acid ester copolymer can be adjusted to 10-70°C by adjusting the monomer ratio when preparing the styrene acrylic emulsion.
[0081] The present engineer has found that the glass transition temperature of the styrene acrylic acid ester copolymer is related to the flexibility of the produced negative electrode sheet. If the Tg of the styrene acrylic acid ester copolymer is too low, the styrene acrylic acid ester copolymer may dissolve when the electrolyte swelling is large, and the stability of the negative electrode active material layer in the secondary battery is poor. If the Tg of the styrene acrylic acid ester copolymer is large, the negative electrode sheet is likely to be hard and brittle, which also affects the processing performance of the battery, such as cold press cutting, winding breakage, and powder falling due to die cutting. Therefore, it is preferable to use a styrene acrylic acid ester copolymer with a glass transition temperature Tg of 10-70°C as the adhesive, and the produced negative electrode sheet not only has good stability but also has good flexibility, which can fully meet the processing and manufacturing requirements.
[0082] Preferably, the glass transition temperature Tg of the styrene acrylic acid ester copolymer used may be 10°C, 12°C, 15°C, 16°C, 17°C, 18°C, 19°C, 20°C, 25°C, 28°C, 30°C, 40°C, 50°C, 60°C, or 70°C. Also, the glass transition temperature Tg of the latex particles (styrene acrylic acid ester copolymer) in the styrene acrylic emulsion used is 10-60°C. Within this further selected range, the negative electrode sheet produced has better flexibility, and the secondary battery produced has a smaller DCR and better cycle performance, and a smaller DCR indicates a better large current discharge capacity, so that the secondary battery can have both good cycle stability and large current discharge capacity.
[0083] In some embodiments, the hard carbon material is at least one of irregularly shaped particles, spherical particles, and nearly spherical particles. In addition, when the hard carbon material is irregularly shaped particles, such as particles with corners, the problems of hardness and brittleness that exist when using conventional adhesives become more pronounced and serious. The styrene acrylic emulsion provided in the present application is particularly suitable for improving the problems of adhesive strength and cohesive strength of the negative electrode sheet caused by such hard carbon materials, and the improvement in adhesive strength and cohesive strength by using this styrene acrylic emulsion as an adhesive is also more pronounced.
[0084] Furthermore, through extensive research, the engineers of the present application have found that when the styrene-acrylic emulsion having a particle size of Dv50 of 350-900 nm is used as an adhesive in the negative electrode sheet of the present application and the hard carbon material is an irregular particle, the adhesive strength between the negative electrode active material layer and the negative electrode current collector in the manufactured negative electrode sheet is 10-40 N / m, and the cohesive strength of the negative electrode active material layer is 150-800 N / m.
[0085] Furthermore, after extensive research, the engineers of the present application have found that in the above-mentioned negative electrode sheet of the present application, a styrene-propylene emulsion having a particle size of 350-900 nm and a Dv50 of the above-mentioned particle size is used as an adhesive, the hard carbon material is at least one of spherical particles and near-spherical particles, and in the manufactured negative electrode sheet, the adhesive strength between the negative electrode active material layer and the negative electrode current collector is 10-30 N / m, and the cohesive strength of the negative electrode active material layer is 150-600 N / m.
[0086] Furthermore, the particle size of the hard carbon material, Dv50, is 1-10 μm, preferably 4-9 μm.
[0087] As shown in Fig. 1, a scanning electron microscope (SEM) of the negative electrode active material layer in one specific example of the negative electrode sheet (specifically, the negative electrode sheet produced in Example 2 described later) is shown in Fig. 1, and as can be seen from the SEM, the hard carbon material is an irregularly shaped particle having corners, the particle diameter of the Dv50 is 5 μm, and the styrene acrylic acid ester copolymer as an adhesive is inserted into the surface of the hard carbon particles after cold pressing, and the particle diameter of the Dv50 of the styrene acrylic acid ester copolymer is 450 nm. As can be seen from the figure, the dispersibility of the styrene acrylic acid ester copolymer is very good.
[0088] The above materials are commercially available unless otherwise specified.
[0089] Positive electrode sheet In a secondary battery, the positive electrode sheet usually includes a positive electrode current collector and a positive electrode film layer provided on the positive electrode current collector, and the positive electrode film layer includes a positive electrode active material.
[0090] The positive electrode current collector can be a conventional metal foil or a composite current collector (a composite current collector can be formed by applying a metal material to a polymer substrate). As an example, the positive electrode current collector can be an aluminum foil.
[0091] The specific type of the positive electrode active material is not limited, and any active material that can be used for a positive electrode of a secondary battery known in the art may be used, and those skilled in the art may select the material according to actual needs.
[0092] As an example, the positive electrode active material may include a lithium ion active material, and the lithium ion active material may include, but is not limited to, one or more of lithium transition metal oxides, lithium-containing phosphates with an olivine structure, and their modified compounds. Examples of lithium transition metal oxides include, but are not limited to, one or more of lithium cobalt oxide, lithium nickel oxide, lithium manganese oxide, lithium nickel cobalt oxide, lithium manganese cobalt oxide, lithium nickel manganese oxide, lithium nickel cobalt manganese oxide, lithium nickel cobalt aluminum oxide, and their modified compounds. Examples of lithium-containing phosphates with an olivine structure include, but are not limited to, one or more of lithium iron phosphate, lithium iron phosphate and carbon composite, lithium manganese phosphate, lithium manganese phosphate and carbon composite, lithium manganese iron phosphate, lithium manganese iron phosphate and carbon composite, and their modified compounds. All of these are commercially available.
[0093] The positive electrode active material may further contain a sodium ion active material, and as the sodium ion active material, a positive electrode active material for a sodium ion battery known in the art can be adopted. As an example, the sodium ion active material is of the Prussian blue (PBA) type ((NaxMA[MB(CN)6]·zH2O (MA and MB are transition metal ions)), which is a compound composed of sodium, transition metal, and cyano groups. For example, Na4Fe2(CN)6, Na4Fe(CN)6, Na1.72MnFe2(CN)6, NaMnMn(CN)6, NaNiFe(CN)6, etc. It is of the oxide type (NaxMO2 (0 < x ≦ 1, M is a transition metal element)), which is composed of a transition metal oxide. Such a variable valence transition metal is mainly vanadium (V), chromium (Cr), manganese (Mn), iron (Fe), cobalt (Co), nickel (Ni), and copper (Cu). Among these, the use of manganese and iron with abundant resources is the most common. For example, NaCrO2, NaMnO2, NaMnO2, Na 0.61 Ti 0.48 Mn 0.52 O2, Na[Fe 0.5 Co 0.5 O2, NaMnO2, Na[Ni 0.25 Fe 0.5 Mn 0.25 O2, etc. And it is of the polyanion compound type (Na x M y 〔(XO m ) n- 〕 z (M is a metal ion with a variable valence, and X is an element such as P, S, and V)), which is composed of sodium, transition metal, and anion. Here, the transition metal is mainly iron, vanadium, cobalt, etc., and the anion is mainly a phosphate group, pyrophosphate group, fluorophosphate group, and sulfate group. For example, NaMnFe2(PO4)6, Na2MnP2O7, Na3V2(PO4)3, Na2Fe2(SO4)3, NaFePO4, Na3V2(PO4)2F3, Na4Co3(PO4)2(P2O7).
[0094] In some embodiments, the modified compound of each of the above materials can be subjected to doping modification and / or surface coating modification with respect to the material.
[0095] The positive electrode membrane layer may typically include an adhesive, a conductive agent, and other optional auxiliary agents.
[0096] By way of example, the conductive agent may be one or more of superconducting carbon, acetylene black, carbon black, ketjen black, carbon dots, carbon nanotubes, Super P (SP), graphene, and carbon nanofibers.
[0097] By way of example, the adhesive may be one or more of styrene butadiene rubber (SBR), water-based acrylic resin, polyvinylidene fluoride (PVDF), polytetrafluoroethylene (PTFE), ethylene-vinyl acetate copolymer (EVA), polyacrylic acid (PAA), carboxymethyl cellulose (CMC), polyvinyl alcohol (PVA), and polyvinyl butyral (PVB).
[0098] Separator In some embodiments, the secondary battery further includes a separator. In the present application, the type of the separator is not particularly limited, and any known porous structure separator having good chemical stability and mechanical stability can be selected.
[0099] In some embodiments, the material of the separator may be at least one selected from glass fiber, nonwoven fabric, polyethylene, polypropylene, and polyvinylidene fluoride. The separator may be a single-layer film or a multi-layer composite film, and is not particularly limited. When the separator is a multi-layer composite film, the materials of each layer may be the same or different, and is not particularly limited.
[0100] electrolyte The secondary battery may include an electrolyte that conducts ions between the positive electrode and the negative electrode. The electrolyte may include an electrolyte salt and a solvent.
[0101] By way of example, the electrolyte salt may be one or more selected from lithium hexafluorophosphate (LiPF6), lithium tetrafluoroborate (LiBF4), lithium perchlorate (LiClO4), lithium hexafluoroarsenate (LiAsF6), lithium bis(fluorosulfonyl)imide (LiFSI), lithium bis(trifluoromethanesulfonyl)imide (LiTFSI), lithium trifluoromethanesulfonate (LiTFS), lithium difluorooxalate borate (LiDFOB), lithium bisoxalate borate (LiBOB), lithium difluorophosphate (LiPO2F2), lithium difluorooxalate phosphate (LiDFOP), and lithium tetrafluorooxalate phosphate (LiTFOP).
[0102] By way of example, the solvent may be one or more selected from ethylene carbonate (EC), propylene carbonate (PC), ethyl methyl carbonate (EMC), diethyl carbonate (DEC), dimethyl carbonate (DMC), dipropyl carbonate (DPC), methyl propyl carbonate (MPC), ethyl propyl carbonate (EPC), butylene carbonate (BC), fluoroethylene carbonate (FEC), methyl formate (MF), methyl acetate (MA), ethyl acetate (EA), propyl acetate (PA), methyl propionate (MP), ethyl propionate (EP), propyl propionate (PP), methyl butyrate (MB), ethyl butyrate (EB), 1,4-butyrolactone (GBL), sulfolane (SF), dimethyl sulfone (MSM), methyl ethyl sulfone (EMS) and diethyl sulfone (ESE).
[0103] In some embodiments, the electrolyte further includes an additive. For example, the additive may include an anode film-forming additive, may include a cathode film-forming additive, or may include an additive capable of improving certain performance of the battery, such as an additive that improves the overcharge performance of the battery, an additive that improves the high temperature performance of the battery, or an additive that improves the low temperature performance of the battery.
[0104] In some embodiments, the secondary battery of the present application is a lithium ion secondary battery.
[0105] A secondary battery can be manufactured according to conventional methods in this field, for example, by sequentially winding (or stacking) a positive electrode sheet, a separator, and a negative electrode sheet, with the separator being positioned between the positive electrode sheet and the negative electrode sheet to serve as an insulator, to obtain a cell, which is then placed in an outer casing, and an electrolyte is injected and sealed to obtain a secondary battery.
[0106] The embodiment of the present application does not particularly limit the shape of the secondary battery, which may be cylindrical, rectangular, or any other shape. Fig. 2 shows a secondary battery 5 having a rectangular structure as an example.
[0107] In some embodiments, the secondary battery may include an exterior case that is used to seal the positive electrode sheet, the negative electrode sheet, and the electrolyte.
[0108] 3, in some embodiments, the exterior may include a case 51 and a cover plate 53. The case 51 may include a bottom plate and a side plate connected to the bottom plate, and the bottom plate and the side plate surround and form a storage cavity. The case 51 has an opening communicating with the storage cavity, and the cover plate 53 is disposed to cover the opening and can seal the storage cavity.
[0109] The positive electrode sheet, the negative electrode sheet and the separator can be formed into an electrode assembly 52 by a winding process or a lamination process. The electrode assembly 52 is packaged in the receiving cavity. The electrolyte is impregnated in the electrode assembly 52. The number of electrode assemblies 52 included in the secondary battery 5 may be one or more, and can be adjusted as needed.
[0110] In some embodiments, the exterior of the secondary battery may be a hard case, such as a hard plastic case, an aluminum case, a steel case, etc. The exterior of the secondary battery may be a soft pack, such as a bag-type soft pack. The material of the soft bag may be plastic, and may include, for example, one or more of polypropylene (PP), polybutylene terephthalate (PBT), polybutylene succinate (PBS), etc.
[0111] In some embodiments, the secondary batteries may be assembled into a battery module, and the number of secondary batteries included in the battery module may be multiple, and the specific number can be adjusted according to the application and capacity of the battery module.
[0112] 4 shows an example of a battery module 4. In the battery module 4, the secondary batteries 5 may be arranged in sequence along the longitudinal direction of the battery module 4. Of course, they may be arranged in any other manner. Furthermore, the secondary batteries 5 may be fixed by fasteners.
[0113] Preferably, the battery module 4 may further include a casing having an accommodation space in which the multiple secondary batteries 5 are accommodated.
[0114] In some embodiments, the battery modules may be assembled into a battery pack, and the number of battery modules included in the battery pack can be adjusted according to the application and capacity of the battery pack.
[0115] 5 and 6 show an example of a battery pack 1. The battery pack 1 may include a battery box and a plurality of battery modules 4 provided in the battery box. The battery box includes an upper housing 2 and a lower housing 3, and the upper housing 2 is covered by the lower housing 3 to form an enclosed space for accommodating the battery modules 4. The plurality of battery modules 4 may be arranged in the battery box in any manner.
[0116] power consumption equipment The present application further provides a power consumption device including at least one of the secondary battery, battery module, or battery pack. The secondary battery, battery module, or battery pack may be used as a power source for the device, or may be used as an energy storage unit for the device. The device may be, but is not limited to, a mobile device (e.g., a mobile phone, a laptop, etc.), an electric vehicle (e.g., a pure electric vehicle, a hybrid electric vehicle, a plug-in hybrid electric vehicle, an electric bicycle, an electric scooter, an electric golf cart, an electric truck, etc.), an electric train, a ship and a satellite, an energy storage system, etc.
[0117] The device can select a secondary battery, a battery module or a battery pack according to its usage needs.
[0118] 7 shows an example of an apparatus. The power consumption apparatus 6 can be a pure electric vehicle, a hybrid electric vehicle, or a plug-in hybrid electric vehicle, etc. To meet the requirements for high power and high energy density of the secondary battery of the apparatus, a battery pack or a battery module can be adopted.
[0119] Other example devices may be mobile phones, tablet computers, notebook computers, etc. These devices are generally required to be thin and can use secondary batteries as a power source.
[0120] The beneficial effects of the present invention will be further illustrated below with reference to examples.
[0121] Working Example In order to clarify the technical problems, technical solutions and beneficial effects solved by the present application, the present application will be described in more detail with reference to the following embodiments and drawings. Obviously, the described embodiments are only some of the embodiments of the present application, but not all of the embodiments. The following description of at least one exemplary embodiment is only explanatory in nature, and does not limit the present application and its application. Based on the embodiments of the present application, all other embodiments obtained by those skilled in the art without creative efforts belong to the scope of protection of the present application.
[0122] All materials used in the examples of this application are commercially available.
[0123] 1. Preparation and performance test of styrene-acrylic emulsion 1. Preparation of styrene-acrylic emulsion 1-9 The preparation monomers of styrene-acrylic emulsion 1-9 include, by mass percentage, 30-80% styrene-based monomer, 20-70% acrylate-based monomer and 0-10% functional monomer. In addition to the preparation monomers, the production raw materials of styrene-acrylic emulsion further include emulsifier, initiator, pH adjuster and water.
[0124] The initiator is ammonium persulfate, the mass of which is 0.5% of the total mass of the monomers prepared. The emulsifier is allyloxynonylphenol polyoxyethylene ether ammonium sulfate, and its mass is 0.7%-5% of the total mass of the prepared monomers. The specific content is shown in Table 1.
[0125] The pH adjuster is sodium hydroxide, the mass of which is 0.2% of the total weight of the prepared monomers.
[0126] The mass of water was 150% of the total weight of the monomers prepared.
[0127] The preparation procedure is as follows.
[0128] Pre-emulsification process: 3 / 4 mass of water, emulsifier, acrylic ester monomer, styrene monomer, and functional monomer are stirred at 50°C for 1 hour to produce a homogeneous, stable pre-emulsion that does not separate into layers, and this is temporarily stored.
[0129] Preparation of seed emulsion: 1 / 4 mass of water, emulsifier, acrylate monomer, styrene monomer, and functional monomer were stirred at 50° C. for 1 hour, and 1 / 4 mass of initiator was added to start polymerization to obtain a seed emulsion.
[0130] Continuous dropping stage: The pre-emulsion was dropped into the seed emulsion, the dropping time was set to 2 hours, and 3 / 4 mass of the remaining initiator was added. After the dropping was completed, the reaction was carried out for 0.5 hours, and the mixture was kept at 85°C for 3 hours to remove the unreacted free monomer.
[0131] Final treatment steps: The system is cooled to 40°C, adjusted to between 8-9 with a pH adjuster, filtered and discharged.
[0132] Styrene acrylic emulsions 1-9 are differentiated by the amount of emulsifier used, as shown in Table 1.
[0133] 2. Performance test of styrene acrylic emulsion 1) The styrene-acrylic emulsion prepared above is measured by a laser particle size analyzer to obtain the particle size, and the instrument is Mastersizer 3000. The specific steps are: inputting the sample parameters of the styrene-acrylic emulsion during measurement includes a refractive index of 1.42, an optical absorptivity of 0.1, and the dispersant is water, and the refractive index of the dispersant is 1.33; there is no need to treat the sample to be measured separately; just add it directly to the sample cell after uniformly stirring until the light shielding degree is 5%-20%, and start the measurement; and record the results after the measurement is completed. The particle size Dv50 of latex particles (styrene-acrylic ester copolymer) in the styrene-acrylic emulsion was measured.
[0134] 2) The styrene-acrylic emulsion prepared above is dried at 80°C for 12 hours to prepare an adhesive film, and the glass transition temperature of the styrene-acrylic ester copolymer therein is measured by differential scanning calorimetry (DSC200F3).
[0135] The preparation monomers, preparation parameters and performance measurement results of styrene acrylic emulsions 1-9 are shown in Table 1 below.
[0136] [Table 1] 2. Manufacture and performance measurement of negative electrode sheet 1. Manufacturing of negative electrode sheets Negative electrode sheet 1-9
[0137] A mass percentage of 94% of hard carbon material 1 (negative electrode active material), 1.0% of conductive carbon black (SP), styrene acrylic emulsion (adhesive, each of which is styrene acrylic emulsion 1-9 produced by the above preparation process, and the mass of styrene acrylic acid ester copolymer in it is 4%.) and 1.0% of sodium carboxymethylcellulose were mixed and dissolved in deionized water to produce a negative electrode slurry. Next, the negative electrode slurry was applied to a copper foil with a thickness of 6 μm, dried and cold pressed to form a negative electrode active material layer, and cut into a negative electrode sheet 1-9.
[0138] Here, the hard carbon material 1 is made of irregularly shaped particles, and the particle size Dv50 is 5 μm.
[0139] Negative electrode sheet 10-11 The negative electrode sheet 10 is basically the same as the negative electrode sheet 2, except that the hard carbon material 1 is replaced with an equal mass of hard carbon material 2, which is spherical particles with a Dv50 particle size of 6 μm.
[0140] The negative electrode sheet 11 is basically the same as the negative electrode sheet 2, except that the hard carbon material 1 is replaced with an equal mass of hard carbon material 3, the hard carbon material 3 being substantially spherical particles with a Dv50 particle size of 5 μm.
[0141] Negative electrode sheet 12-15 The negative electrode sheet 12 is basically the same as the negative electrode sheet 2, with the difference being that a styrene-butadiene emulsion is used instead of the styrene-acrylic emulsion 2 in the negative electrode sheet 2, and the mass content of the emulsion balls in the styrene-butadiene emulsion in the negative electrode sheet is 4%. The Dv50 particle size of the latex particles in the styrene-butadiene rubber emulsion was 120 nm.
[0142] The negative electrode sheet 13 is basically the same as the negative electrode sheet 2, except that a styrene-acrylic emulsion 10 having a Dv50 particle size of 280 nm is used instead of the styrene-acrylic emulsion 1 in the negative electrode sheet 1, and the mass content of the styrene-acrylic ester copolymer therein in the negative electrode sheet is 4%.
[0143] The negative electrode sheet 14 is basically the same as the negative electrode sheet 10, except that a styrene-acrylic emulsion 10 having a Dv50 particle size of 280 nm is used instead of the styrene-acrylic emulsion 2 in the negative electrode sheet 10, and the mass content of the styrene-acrylic acid ester copolymer in the negative electrode sheet is 4%.
[0144] The negative electrode sheet 15 is basically the same as the negative electrode sheet 11, except that a styrene-acrylic emulsion 11 having a Dv50 particle size of 200 nm is used instead of the styrene-acrylic emulsion 2 in the negative electrode sheet 11, and the mass content of the styrene-acrylic acid ester copolymer in the negative electrode sheet is 4%.
[0145] Negative electrode sheet 16 The negative electrode sheet 16 is basically the same as the negative electrode sheet 2, except that the hard carbon material 1 therein is replaced with an equal mass of graphite, the Dv50 particle size of which is 13 μm.
[0146] 2. Performance measurement of negative electrode sheet 1) The flexibility of the negative electrode sheet was measured as follows.
[0147] The flexibility of the negative electrode sheet produced above was measured using a curl pin. A sheet sample measuring 40 mm in length and width and 100 mm in length was produced and wrapped around a specially made curl pin. The electrode sheet was then visually and microscopically observed for cracks to determine its flexibility level.
[0148] The diameter of the curl pin is R.
[0149] When R≦1.0mm, the electrode sheet will not crack and has the best flexibility, which meets the production needs.
[0150] If there is a crack at R=1.0mm and no crack at R=2.0mm, the flexibility is second-class and meets the production needs.
[0151] If there is a crack at R=2.0mm and a crack at R=3.0mm, the flexibility is third-class, which does not meet production needs.
[0152] If there is no crack at R=3.0mm and there is a crack at R=4.0mm, the flexibility is fourth-class, which does not meet production needs.
[0153] The method for producing the curl pin is as follows.
[0154] Conventional 304 stainless steel rods having diameters of 1.0 mm, 2.0 mm, 3.0 mm, and 4.0 mm were cut to 60 mm and fixed by welding to a steel plate of 150 mm x 300 mm to obtain the curl pins.
[0155] The smaller the diameter of the curl pin used, the less the electrode sheet cracks, indicating that the electrode sheet has good flexibility, and conversely, the larger the diameter of the curl pin used, the more the electrode sheet cracks, indicating that the electrode sheet has poor flexibility.
[0156] 2) Method for measuring adhesive strength of negative electrode sheet The negative electrode sheet produced above was weighed along the direction perpendicular to the machine direction (TD), and a sample with a size of 20 mm (width) x (100-160) mm (length) was cut out, and a special double-sided tape was attached to a steel plate, with the size of the tape being 20 mm (width) x (90-150) mm (length). After the cut electrode sheet sample was attached to the double-sided tape, it was rolled three times in the same direction with a 2 kg hand roller. The adhesive strength of the electrode sheet was measured using a tensile machine, and the greater the adhesive strength between the membrane layer and the current collector in the hard carbon electrode sheet, the stronger the force between the active material and the current collector in the hard carbon electrode sheet, and conversely, the worse the force between the active material and the current collector in the electrode sheet.
[0157] 3) Cohesive force measurement method The negative electrode sheet produced above is weighed along the direction perpendicular to the machine direction (TD), a sample with a size of 20 mm (width) x 100 mm (length) is cut out, and a special double-sided tape is attached to a steel plate, the size of the double-sided tape is 20 mm (width) x 100 mm (length). The cut electrode sheet sample is attached to the double-sided tape, and then the green glue tape is attached to the electrode sheet sample, the size of the green glue tape is 20 mm (width) x 120 mm (length), the green glue of the part that does not contact the electrode sheet is attached to a 20 mm (width) x 60 mm (length) piece of paper, the paper piece and the green glue are formed in a collinear line, the joint part between the green glue and the paper piece is glued with wrinkle glue, and contacts the green glue of the electrode sheet part, and before measurement, the electrode sheet and the double-sided tape need to be uniformly compacted. A tensile machine is used to measure the cohesive force of the electrode sheet. The larger the force between the active particles in the membrane layer of the hard carbon electrode sheet, the stronger the interaction force between the active materials in the hard carbon electrode sheet is, and conversely, the weaker the interaction force between the active materials in the electrode sheet is.
[0158] The tapes used to measure adhesive strength and cohesive strength were all commercially available standard tapes.
[0159] 3. Battery Construction 1. Positive electrode sheet: active material LiNi 0.8 Co 0.1 Mn 0.1 O2, conductive carbon black (SP), and polyvinylidene fluoride (PVDF) were mixed in a mass ratio of 96.8:2.2:1, dissolved in N-methylpyrrolidone (NMP), and made into a paste to obtain a positive electrode slurry. The positive electrode slurry was applied to an aluminum foil having a width of 400 mm, dried, cold pressed, and cut to obtain a positive electrode sheet.
[0160] 2. Separator: Polyethylene (PE) porous polymer separator is used as the separator.
[0161] 3. Negative electrode sheet: The negative electrode sheet 1-16 produced above was used.
[0162] 4. Electrolyte: Ethylene carbonate (EC), ethyl methyl carbonate (EMC), and diethyl carbonate (DEC) were mixed in a volume ratio of 3:6:1, and then thoroughly dried lithium salt (LiPF6) was dissolved in the mixed organic solvent at a ratio of 1 mol / L. The desired electrolyte was obtained.
[0163] 5. Full battery assembly: The positive electrode sheet, separator, and negative electrode sheet are stacked in order, the separator is placed between the positive and negative electrodes to serve as an insulator, and then rolled up to obtain a bare cell. The bare cell is placed in an exterior aluminum case, and the above-prepared electrolyte is injected into the dry cell after high-temperature drying. After vacuum sealing, standing, chemical formation, shaping, and other processes, lithium ion secondary battery 1-16 is obtained as shown in Table 2.
[0164] Battery performance evaluation The performance of each of the batteries 1 to 16 was evaluated by the following method.
[0165] 1. Measurement of the battery's direct current resistance (DCR) A capacity test was performed on the battery at 25°C, that is, after the formation capacity of the battery was performed, the battery was left at 25°C for 10 minutes, then charged to 100% SOC (Sate of Charge) at 0.33C, polarized with a small current, left at rest for 10 minutes, and further discharged to 0% SOC at 0.33, and the obtained capacity is the 0.33C capacity of the battery. Then, a constant voltage 0.05C charge was performed, left at rest for 60 minutes, discharged to 50% SOC at 0.33C, left at rest for 60 minutes, discharged to 20% SOC at 0.33C, left at rest for 60 minutes, discharged to 0% SOC at 0.33C, measured the open circuit voltage at 0% SOC, and compiled the DCR data for 30s.
[0166] 2. Cycle performance measurement The first charge and discharge were carried out in a constant temperature environment of 25°C, followed by constant current and constant voltage charging (charging until the current reached 0.05C) at a charging current of 1.0C (i.e., completely discharging the current value of the theoretical capacity within 1 hour), leaving the battery to stand for 5 minutes until the upper limit voltage reached 4.25V, and then discharging at a constant current at a discharge current of 1.0C until the final voltage reached 2.8V. The discharge capacity of the first cycle was recorded, and then the charge and discharge cycles were continued.
[0167] Capacity retention rate at the nth cycle = (discharge capacity at the nth cycle / discharge capacity at the first cycle) x 100%. The test is stopped when the cycle capacity retention rate reaches 80%, and the number of cycles at this point is obtained.
[0168] Some materials and performance measurement results of the negative electrode sheet 1-16 are shown in Table 2 below.
[0169] [Table 2] In the negative electrode sheet 12 of Comparative Example 1, the hard carbon particles themselves are hard and brittle, and therefore the adhesive strength of the negative electrode sheet prepared using styrene-butadiene rubber (SBR) as an adhesive and the cohesive strength of the negative electrode active material layer are both low, and the sheet is abnormally hard and brittle with poor flexibility. As a result, the DCR of the battery produced is large and the cycle performance is poor.
[0170] In Comparative Example 2, the hard carbon material in the negative electrode sheet 13 is made of irregular particles, and a styrene-acrylic emulsion 10 with a particle size of Dv50 of 280 nm is used as an adhesive. The particle size of the styrene-acrylic ester copolymer therein is small, and the adhesive strength and cohesive strength are 3 N / m and 35 nm, respectively. Compared with the Examples, the adhesive strength and cohesive strength are still very low, and the cycle performance is poor.
[0171] In the negative electrode sheets 14-15 in Comparative Examples 3-4, the hard carbon materials were spherical and near-spherical particles, respectively, and styrene-acrylic emulsion 10 having a Dv50 particle size of 280 nm and styrene-acrylic emulsion 11 having a Dv50 particle size of 200 nm were used as adhesives. The adhesive strength and cohesive strength of the negative electrode sheets produced were improved compared to Comparative Examples 1-2, but were lower than those of the Examples, and therefore the cycle performance was poor.
[0172] In the negative electrode sheet 16 of Comparative Example 5, graphite was used as the negative electrode active material and styrene acrylic emulsion 2 was used as the adhesive. The adhesive strength of the negative electrode sheet and the cohesive strength of the negative electrode active material layer were still lower than those of Example 2, indicating that the styrene acrylic emulsion, as an adhesive, has a more excellent improving effect on the adhesive strength and cohesive strength of the negative electrode active material layer of the negative electrode sheet in which the negative electrode active material is hard carbon.
[0173] The Dv50 particle size of the styrene acrylic acid ester copolymer in the styrene acrylic emulsion used in the negative electrode sheet of Examples 1-5 is 350nm-900nm, and both have excellent flexibility, adhesive strength and cohesive strength. Furthermore, compared with Example 5, the negative electrode sheet manufactured in Examples 1-4 has better flexibility, adhesive strength and cohesive strength, and the manufactured secondary battery has a smaller DCR and better cycle performance, and the smaller DCR shows better large current discharge capability. The Dv50 particle size of the styrene acrylic acid ester copolymer is preferably 350nm-800nm.
[0174] The Dv50 particle size of the styrene acrylic ester copolymer in the styrene acrylic emulsion used in the negative electrode sheets of Examples 6-9 is 450 nm, and the main difference is that the comonomer composition of the styrene acrylic ester copolymer is different, and further, its glass transition temperature is different. As can be seen from Examples 6-9, the glass transition temperature of the styrene acrylic ester copolymer is 15-70 ° C., and all have excellent flexibility, adhesive strength, cohesion and cycle performance. Furthermore, compared with Example 9, the negative electrode sheets prepared in Examples 6-7 have better flexibility and cycle characteristics and smaller DCR, so it is preferable that the glass transition temperature of the styrene acrylic ester copolymer is 15-60 ° C.
[0175] In Examples 10-11, the Dv50 particle size of the styrene acrylic acid ester copolymer in the styrene acrylic emulsion used for the negative electrode sheet is within the range of 350 nm to 900 nm, and similarly, it is applied to hard carbon materials of spherical particles and near-spherical particles, and shows that it has a good improving effect on the adhesive strength of the negative electrode sheet and the cohesive strength of the negative electrode active material layer.
[0176] The above are merely specific embodiments of the present application, and the scope of protection of the present application is not limited thereto, and those skilled in the art can easily think of various equivalent modifications or replacements within the technical scope disclosed in the present application, and all of these modifications or replacements should be included in the scope of protection of the present application. Therefore, the scope of protection of the present application is subject to the scope of protection of the claims.
Claims
1. A negative electrode sheet, the negative electrode sheet includes a negative electrode current collector and a negative electrode active material layer located on at least one surface of the negative electrode current collector, The negative electrode sheet is characterized in that the components of the negative electrode active material layer include a hard carbon material and an adhesive derived from a styrene-acrylic emulsion having a Dv50 particle size of 350-900 nm of latex particles.
2. The negative electrode sheet described in claim 1, characterized in that the latex particles are styrene-acrylic ester copolymers, and the glass transition temperature of the styrene-acrylic ester copolymers is 10-70°C.
3. 3. The negative electrode sheet according to claim 2, wherein the components of the negative electrode active material layer further include a conductive agent and a dispersant, and in the negative electrode active material layer, the hard carbon material is 85%-97%, the styrene-acrylic acid ester copolymer is 1%-8%, the conductive agent is 0.3%-5%, and the dispersant is 0.5%-4%, in mass percentage.
4. The coating weight of the negative electrode active material layer is 2-13 mg / cm 2 2. The negative electrode sheet according to claim 1 ,
5. 2. The negative electrode sheet according to claim 1, wherein the hard carbon material is at least one of irregularly shaped particles, spherical particles, and approximately spherical particles.
6. 2. The negative electrode sheet according to claim 1, wherein the hard carbon material has a Dv50 particle size of 1 to 10 μm.
7. The negative electrode sheet according to claim 1, wherein the hard carbon material is a non-circular particle, the adhesive strength between the negative electrode active material layer and the negative electrode current collector is 10-40 N / m, and the cohesive strength of the negative electrode active material layer is 150-800 N / m.
8. The negative electrode sheet according to claim 1, wherein the hard carbon material is at least one of spherical particles and approximately spherical particles, an adhesive strength between the negative electrode active material layer and the negative electrode current collector is 10-30 N / m, and a cohesive strength of the negative electrode active material layer is 150-600 N / m.
9. A secondary battery comprising the negative electrode sheet according to any one of claims 1 to 8.
10. A power consuming device comprising the secondary battery according to claim 9.
Citation Information
Patent Citations
Preparation method of styrene-acrylic emulsion for water-borne wood paint
CN113736009A
Silicon-containing negative pole piece as well as preparation method and application thereof
CN114141988A
Resin particle group and production method thereof
JP2018172691A
Dispersed polymer composition
WO1998014519A1
Method for producing electrode / separator laminate, and lithium-ion rechargeable battery
WO2014081035A1